Understanding the relationship between built environment features and physical activity in the Caribbean: A scoping review - Kern Rocke; Christina Howitt; Ian Hambleton (Elsevier, 2023)
Background: Transforming the urban infrastructure to become safe, inclusive and sustainable remains a challenge in most developing settings. The Caribbean has high burdens of physical inactivity and non-communicable diseases. Therefore, understanding the role of the built environment (BE) in modifying individual activity is important for informing the design of community interventions to improve levels of physical activity (PA). Anecdotally, there is limited evidence on the BE in the Caribbean, however evidence from other Small Island Developing States (SIDS) and from Latin America (LA) may offer useful information given their similar urbanization profiles and shared geo-collaborative histories. Objective: Our review identifies and characterizes individual features of the BE and examines their relationships with PA outcomes. Methods: We systematically searched a range of multi-discipline research databases, including studies from SIDS and LA that objectively measured BE features as an exposure and PA as an outcome between 2010 and 2021. Grey literature was not considered for this review. We characterized BE measures into 9 neighbourhood design domains using the Walkability for Health framework, and mapped gaps in the published evidence. We performed a narrative summary of BE-PA relationships, focusing on association strength and direction of effect. Results: Fifty-one studies from published scientific literature in Brazil, Colombia, Mexico, Chile, and Singapore were included that described 306 BE-PA relationships. The BE was mostly characterized by number of and proximity to spaces for social interaction, green spaces, increasing housing density or street connectivity, and mixed residential and commercial land use. BE-PA relationships, although inconsistent, largely promoted PA. Conclusion: Although the review is suggestive of the benefits of the benefits of BE interventions for promoting active commuting and leisurely PA, translational research is needed to understand whether results can be successfully adapted for SIDS, which often have an urban structure defined by a single urban centre with connections to outlying communities.